Pedagogical Content Knowledge (PCK) of 4th Semester Students in Biology Education Department on the Subject of Biology Learning Strategy - Putri Agustina (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2015)
This study aimed to describe the Pedagogical Content Knowledge (PCK) Biology student teachers in designing learning scenarios at the moment to take a course Biology Learning Strategy. This research is descriptive exploratory study. The population were all fourth semester students who take a course in Biology Learning Strategy totaling 140 students. Samples taken at random sampling two classes (63 students). The data were analyzed descriptively. The results showed that 75% of students are still difficulties in determining the appropriate materials with basic competence selected. Selection of many theoretical material, only 25% of students who chose contextual material and are directly related to the lives of learners. 60% of students on average chose teaching media in the form of power point slides and video. Preparation of the average slide is still much in the form of minimal explanation and illustration. The selected videos most movies are full length making it less effective used in the learning process. Selection of quite varied learning methods, 50% chose a lecture and question and answer, 25% choose the method of guided discovery, and others prefer a combination of lecture with methods that emphasize student activity. In general, students are still confused in determining the proper method in accordance with the characteristics of the material being taught. From the analysis of learning scenarios developed generally known that students have a mastery of the knowledge of the content (C) and pedagogy (P) were quite good however, the link between pedagogy with content (PCK) is still lacking, especially in selecting methods and instructional media in accordance with material characteristics and levels